PELANGGARAN LALU LINTAS OLEH ANAK-ANAK DI BAWAH UMUR DI DESA SIMPANG RIMBA KABUPATEN BANGKA SELATAN - Sri Yuliana (Justici, 2020)
Abstract Land transportation plays a very important role in supporting national development and has the largest contribution in serving human mobility and distribution of trade and industrial commodities in various regions. As stated in Article 77 of RI Law No.22 of 2009 concerning Traffic and Road Transportation that every motorized vehicle driver must have a SIM. With the existence of a driver for children on the streets it is certain that a child who is underage does not have a SIM. How is the application of the law for traffic violators, especially minors in Simpang Rimba Village, South Bangka? The application of the law against traffic violations committed by minors, namely: Exemption from violations, Actions that are not optimal, and maximum Actions.